(untitled) (Global Journal of Human-Social Science, 2012)
This paper is a reflection upon issues of in-service teacher education courses by connecting them, with teachers’ problems that they face in actual classroom environment. It is a revision of literature where the author after reviewing the literature and discussing about methods and material of in-service courses, researcher’s commentary on current teachers" in-service programs, and discussing about reflecting scope f in-service programs and by teachers’ concerns about improvement of these programs, the researcher has proposed a model based on teachers’ concerns and problems that they face in classroom environment. Generally teaching content of in-service courses is designed by funding agency or by course instructors and they generally taught content relating to teaching methodology or explaining some concepts of new curriculum. They ignore teachers’ classroom related problems like students learning and behavioural problems. Therefore, the author developed model has implications for designing of in-service courses of secondary level teachers.